Ecological Footprint and tourism: Development and sustainability monitoring of ecotourism packages in Mediterranean Protected Areas. (June 2022) - Mancini, Maria Serena; Barioni, Debora; Danelutti, Carla; Barnias, Antonios; Bračanov, Valentina; Capanna Piscè, Guido; Chappaz, Gilles; Đuković, Bruna; Guarneri, Daniele; Lang, Marianne; Martín, Isabel; Matamoros Reverté, Sílvia; et al.
Abstract: Ecotourism is a potential lever for sustainable development, but common standards and approaches lack to manage and monitor the impact of defined packages on natural resources and local communities. A customized version of Ecological Footprint Accounting is evaluated here to assess its usefulness as analytical tool to quantitatively analyse the environmental pressures associated with ecotourism packages developed in and around Protected Areas in the Mediterranean Region. Within the framework of the EU-funded DestiMED project, a bottom-up, participatory approach was developed for managing and monitoring 13 ecotourism packages by involving local tourism stakeholders and service providers. The application of Ecological Footprint Accounting relied on data sourced from local service providers to complement existing statistics and datasets, and was used in an empirical iterative process to provide local tourism stakeholders with recommendations to guide them in the management of a low-impact tourism offer. International travel to and from the 13 destinations was found to place a Footprint on the environment – mainly because of carbon emissions – higher than that of the entire stay at destination. Footprint results of the packages revealed some overlooked tourism's impacts on ecosystems due to unexpected drivers, such as the Food & Drink services offered to tourists at destination. Results indicate that managing tourism product development at destination, and investing in providing knowledge on the principles of sustainability, could lower ecotourism's impacts whilst contributing to building resilience and aiding the post-COVID recovery of destinations. Management implications: This article tested the applicability and usefulness of Ecological Footprint Accounting (EFA) to assess ecotourism packages developed in and around Protected Areas (PAs) across the Mediterranean Region. A customized version of Ecological Footprint Accounting is suitable for managers and can be used to quantitatively assess the multiple pressures of the activities included in ecotourism packages through a bottom up approach. This innovative monitoring process typically fosters the engagement with the local service providers, which is key for a sustainability monitoring of the touristic offer. Applied to ecotourism packages, EFA allows identifying the main ecosystems under pressure as well as the main drivers causing such pressures. This information is useful to understand the actual impacts caused by the packages offered in their territory, and – when combined with tangible recommendations for improvements – to help adjust the services offered in the packages to possibly reduce environmental impacts.